Clinical and biochemical status of patients with ulcerative collitis - Yu. A. Khalitova; Yu. V. Myakisheva; S. E. Katorkin; P. S. Andreev; D. S. Gromova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn's disease (CD), are chronic inflammatory conditions of the gastrointestinal tract characterized by a relapsing and remitting course. Aim - to analyze clinical data and the most significant hematological and biochemical blood parameters used for diagnosis in patients with ulcerative colitis. Materials and methods. Between 2020 and 2021 examined 50 patients with the diagnosis "Ulcerative colitis" living in the Samara region. The diagnosis of ulcerative colitis was confirmed by a combination of clinical, radiological, endoscopic, and histopathological criteria generally accepted for inflammatory bowel diseases. A hematological blood test was performed on an automatic hematological analyzer Sysmex KX-21N, Japan, and a biochemical blood test was performed on an automatic biochemical analyzer Hitachi 902, Japan. Results. In the biochemical analysis of blood, an increase in the content of C-reactive protein in the blood is expected in 64% of patients. In 40% of patients, the concentration of total protein and electrolytes decreases. An increase in glucose levels was revealed in 44% of patients, in 10% of cases, a decrease in creatinine concentration, an increase in the activity of ALAT and ASAT was noted in 6 and 4% of cases, respectively. Reduced urea levels are noted in 6% of patients. Conclusion. As a result of the study, the data necessary for the diagnosis and monitoring of the effectiveness of the treatment of ulcerative colitis were obtained.